Evaluation of the accuracy of remote emission sensing measurements via real-world vehicle dynamic tests - Tian, Qili; Yang, Xinping; Jiang, Han; Wang, Xiaohu; Liu, Jin; Zhang, Yingzhi; Cao, Yang; Kang, Yu; Fu, Mingliang; Zhang, Hefeng (Environmental pollution (1987), 2024)
To evaluate the measurement accuracy of horizontal and vertical remote emission sensing (RES) equipment, a real-world dynamic test was carried out in Chengdu by using electric vehicles equipped with various concentrations of standard gases. In addition, a new Image-based Spectral Processing Algorithm (ISPA) for vertical remote sensing spectral data was developed to improve the measurement capability. The results showed that the ISPA provided a greater percentage of valid data and lower relative errors; thus, our new algorithm could more effectively analyze the spectral data to measure vehicle emission levels. The percentages of valid horizontal and vertical RES data were 71% and 84%, respectively. The mean relative errors of CO2, CO, HC and NO measured by the vertical RES were about 5%, 20%, 20% and 40%, respectively, and those of CO2, CO and NO measured by the horizontal RES were 3%, 13% and 15%, respectively. For the common vehicle emission concentration, the percentage of valid data for the two RES types increased with increasing gas concentration. As the vehicle speed increased, the relative errors of the horizontal RES equipment showed an increasing trend for the same concentration of gas. Furthermore, for the same speed segment, the relative errors of the horizontal RES equipment increased as the simulated emission concentration decreased. The vertical RES equipment did not exhibit a consistent trend in terms of changes. This study provides a data quality reference for further RES applications. [Display omitted] •Accuracy of horizontal and vertical remote emission sensing were evaluated.•A new vertical RES spectral data algorithm was developed to reduce NO error.•Mean relative errors of NO from V-RES and H-RES were 15% and 40%, respectively.•Both RES equipment can better evaluate fleet emissions and screen higher emitters.